Hubungan Kebiasaan Makan Pagi terhadap Konsentrasi Belajar pada Mata Pelajaran Matematika Siswa Kelas III SDN Bidara - Aam Amaliyah; Emilia Septia Rini; Moh. Zamroni (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
The purpose of this investigation is to determine whether or not students in the third grade at SDN Bidara have a habit of eating breakfast and whether or not it affects their ability to concentrate on learning mathematics subjects. Quantitative research methods were utilized throughout the course of this investigation. In order to collect the necessary information for this study, we will be using questionnaires, interviews, and documentation. Analysis of the data performed using product moment analysis. The simple linear regression analysis, the t test, and the coefficient of determination are the analytical methods that were utilized (R2). According to the findings of this research project, the routine of eating breakfast appears to have a significant correlation with the ability to concentrate while studying mathematics. This is supported by the fact that the calculation for tcount was 0.594, which is greater than ttable, which was 0.349. As a result, it is possible to draw the conclusion that Hypothesis 1 (H1) is correct, which states that eating patterns at breakfast affect the concentration required for learning mathematics by 35.3%, while the remaining 64.7% is influenced by other factors that were not investigated in the study.